Pembangunan Prasarana Ruang Pembelajaran Di TPQ An-Noerwahid Desa Gunung Malang Kabupaten Bogor - Tommy Iduwin (Sekolah Tinggi Teknik - PLN, 2021)
Infrastructure is a facility that indirectly supports the educational process, such as: school gardens, roads to schools, study rooms, and others. Infrastructure is a part very important role for the success and smoothness of a process, including in the scope of education. Infrastructure is a facility that is absolutely fulfilled to provide convenience in carrying out an activity. TPQ An-Noerwahid Gunung Malang Village, Bogor Regency, is the target location for Community Service activity partners who do not yet have good infrastructure. When conducting a review of the TPQ, it was seen that the building in the study room was very unfit to be used as a place for learning for TPQ students. With limited money by local residents, it is very difficult for partners to develop the study room. Good infrastructure will make these students enthusiastic and no longer hampered by natural disturbances such as wind, rain, etc Keywords: Infrastructure, Construction, Study Room